Adaptive speciation - Dieckmann, Ulf, 1966- (Cambridge studies in adaptive dynamics., 2004)
"Adaptive Speciation elucidates how selection driven by biological interactions can trigger the adaptive splitting of lineages. Recent advances in speciation theory are carefully explained and confronted with celebrated empirical examples of speciation under natural selection. With an emphasis on the potentially intricate interplay between geographic patterns and ecological processes of speciation, this book seeks to move beyond the default perception of speciation as a mere side effect of geographic isolation. The resulting perspective enables adaptive speciation to be appreciated as a major force in the generation of biological diversity. Written for students and researchers alike, this book provides a thorough treatment of the newest developments in speciation science."--Jacket